The effect of zinc and copper supplementation to ration on blood acid-base and some plasma electrolyte levels in lambs - Nurcan Dönmez; Zafer Durgun; Ramazan Çöl (Eurasian Journal of Veterinary Sciences)
In the present study, Zn and Cu supplemented into lamb ration containing optimum level of Zn and Cu (35 ppm and 9 ppm respectively) and their eflects on acid-base balance and some electrolytes were aimed to investigate. 24 Konya Merinos lambs 3,5 months aged and weighing 26 kg body weight were used as material. The animals were divided into 4 equal groups. First group (control. K) with basal ration (70 % forage. 30 % concentrated feed), the second group (group Zn) with basal ration plus Zn supplementation (250 mg/kg in dry matter of the ration), 31*1 group (group Cu) with basal ration plus Cu supplementation (25 mg/kg in dry matter of the ration) and the 4m group (group Zn + Cu) with Zn and Cu supplementation (250 mg/kg Zn and 25 mg/kg Cu in dry matter of the ration) were fed ad libitum for 3 months. Plasma Zn levels in group Zn and in group Zn + Cu were 1,61± 0,07 and 1.54 ± 0.04 pg/ml respectively and these values were significantly higher (p<0.05) compared the same values obtained from group K and group Cu. Furthermore plasma Cu levels in group Cu and in group Zn + Cu were 0.96 ± 0.08, 0.80 ± 0.07 pg/ml respectively and these values were also high compared the same values obtained from other groups. Blood pH, plasma HCO'3 and Na values in all groups were not statistically different. In addition other parameters examined in this study were also similar in all groups. As a result, Zn and Cu supplementation into a ration containing normal levels of Zn and Cu had no important effect on acid-base balance and plasma electrolyte levels in lambs.